Synthesis and Characterization of Some Metal Complexes of [4-Methoxy-N-(pyrimidine-2-ylcarbamothioyl)benzamide] (Baghdad Science Journal, 2025)
A new ligand [4-Methoxy -N-(pyrimidine-2-ylcarbamothioyl) benzamide] (MPB) was synthesized by reactioniofi(4-Methoxyibenzoyliisothiocyanate)withi(2-aminopyri-midine). The Ligand was characterized by elemental micro analysis (C.H.N.S),(FT-IR) (UV- Vis) and (1Hi,13CNMR)spectra. Some transition metals complexes of this ligand were prepared and characterized by (FT-IR, UV-Vis) spectra conductivity measurements magnetic susceptibility and atomic absorption. From the obtained results the molecular formula of all complexes was suggested to be [M(MPB)2Cl2] (M+2i=Cu, Mn, Co ,Ni ,Zn ,Cd and Hg),the proposed geometrical structure for all complexes was an octahedral.